Confessions of a Murder Suspect - James Patterson; Maxine Paetro (Confessions series, 2013)
Tandy Angel is, along with her brothers, a suspect in their parents' murder but having grown up under Malcolm and Maud Angel's perfectionist demands, Tandy decides she must clear the family name no matter what.